High-performance work practices and employee wellbeing: organizational identification as a mediator - Salin, Denise; Stride, Chris; Smith, Sofia; Santokhie, Stefan (Frontiers in Psychology, 2023)
Aim The aim of this study was to examine how high-performance work practices affect engagement and workplace bullying, two different aspects of employee wellbeing. Furthermore, the study sought to examine the potential mediating role of organizational identification in these relationships. Method A two-wave survey study (n = 213) was conducted among psychologists in Finland. Results The results showed that high-performance work practices (HPWPs) were positively associated with engagement and negatively associated with the risk of workplace bullying. Moreover, organizational identification acted as mediator of the HPWPs-engagement relationship, though alongside the significant indirect effect via organizational identification there was also a significant direct effect of HPWPs on engagement. Discussion The study adds knowledge to ongoing debates on whether HPWPs support or undermine employee wellbeing. In particular, it extends our understanding of the association between HPWPs and relationship wellbeing, a topic that has so far received scant attention. Furthermore, the study advances our understanding of explanatory mechanisms in the HPWPs-engagement relationship and points to the importance of organizational identification for explaining why HPWPs lead to higher engagement.